Extreme temperature differences in the city of Lahti, southern Finland: Intensity, seasonality and environmental drivers - Juuso Suomi (Elsevier BV, 2022)
The extremes of month-specific spatial temperature differences were studied for a first time in the high-latitude city of Lahti and its surroundings in southern Finland. During the 2-year observation period (6/14–5/16), the largest momentary temperature difference, 11.1 °C, was detected in February, and the smallest, 6.2 °C, in April. The impacts of various environmental factors during the extreme situations were estimated by site-specific analysis of the warmest and coldest observation sites and a stepwise multiple linear regression model including all the 8 observation sites. The extreme temperature differences were characterised by inversions especially in winter and spring, the warmest site being the hill-top location in Kivistönmäki. In summer the role of urban heating was more apparent, and the temperature was the highest in the relatively low-lying city centre. In autumn the heating impact of the relatively warm Lake Vesijärvi caused the largest temperature differences with harbour as the warmest site. The weather during all of the momentary extreme situations was calm and in the majority of the situations also clear. The impact of cloud cover was less critical than that of wind speed in reducing spatial temperature differences. The momentary extreme situations existed at night or at dawn, with one exception: only in January, during the cold weather period dominated by high pressure, the delayed break of inversion in the vicinity of Lake Vesijärvi caused the extreme temperature difference to exist in the afternoon, reflecting for its part the substantial stabilising impact of seasonal ice cover on Lake Vesijärvi.